Genomic comparison of carbapenem-resistant Enterobacteriaceae from humans and gulls in Alaska. (June 2021) - Ahlstrom, Christina A.; Frick, Anna; Pongratz, Catherine; Spink, Kimberly; Xavier, Catherine; Bonnedahl, Jonas; Ramey, Andrew M.
Highlights: CPE from humans and gulls shared conserved genetic elements surrounding bla KPC . Genomic analysis did not evince direct transmission of CPE between humans and gulls. Wildlife may serve as indicators of clinically important AMR in the environment. Abstract: Objectives: Wildlife may harbour clinically important antimicrobial-resistant bacteria, but the role of wildlife in the epidemiology of antimicrobial-resistant bacterial infections in humans is largely unknown. In this study, we aimed to assess dissemination of the bla KPC carbapenemase gene among humans and gulls in Alaska. Methods: We performed whole-genome sequencing to determine the genetic context of bla KPC in bacterial isolates from all four human carbapenemase-producing Enterobacteriaceae (CPE) infections reported in Alaska between 2013–2018 and to compare the sequences with seven previously reported CPE isolates from gull faeces within the same region and time period. Results: Genomic analysis of CPE isolates suggested independent acquisition events among humans with no evidence for direct transmission of bla KPC between people and gulls. However, some isolates shared conserved genetic elements surrounding bla KPC, suggesting possible exchange between species. Conclusion: Our results highlight the genomic plasticity associated with bla KPC and demonstrate that sampling of wildlife may be useful for identifying clinically relevant antimicrobial resistance not observed through local passive surveillance in humans.